Ingested Foreign Bodies Can Cause Appendicitis and Perforation: A Multi-Institutional Case Series. (September 2022) - Fuller, Maren Y.; Leino, Daniel G; Reyes-Múgica, Miguel; Kovach, Alexandra E.; Velázquez Vega, José E.; Caltharp, Shelley; Bhatti, Tricia; Gonzalez, Raul S
Introduction: Appendicular foreign bodies are a rare, under-described cause of appendicitis. We performed this study to determine the varied causes and consequences of foreign-body appendicitis. Methods: On retrospective review of the pathology archives of seven institutions, we identified 56 appendix specimens containing a foreign body (defined as ingested, non-digestible material). We recorded the type of foreign body, patient age and sex, and other findings, as available. Results: Mean patient age was 7.7 years (range: 1 day–18 years). The foreign bodies included hair, plant material, magnets, other metallic material, BB pellets, foreign material not otherwise specified, and other miscellaneous objects. Of 48 cases with available clinical information, 31 patients presented with abdominal pain, and 22 were preoperatively diagnosed as having appendicitis/appendicular inflammation. Seven patients had appendiceal perforation (13%). The foreign body was grossly identified in 34/47 cases with available gross descriptions. Twenty-seven cases had an identifiable foreign body microscopically; 10 were associated with giant cell reaction. Discussion: Hair and plant materials were the most common foreign objects found in the appendix; they often cause mucosal damage and giant cell reaction. Metallic objects were less common. Although appendicular foreign bodies in children are rare and sometimes asymptomatic, they may lead to perforation.